Capacidade antioxidante de pêssegos de polpa amarela, em três estádios de maturação e minimamente processados. - Santos, Roberta Oliveira (2011)
The maturation can be characterized as a sequence of changes that occur the last stages of development to the early stages of senescence, resulting in quality characteristics of the fruit. The best stage to harvest peaches depends mainly on the fate that will be given. The mature fruits are given to meet consumer demands, as those intended for storage should be firm to prevent physiological disorders and increase their potential for storage and longer shelf life. Thus the present study was aimed to detect changes that occur during the ripening fruits with emphasis on the synthesis and degradation of bioactive compounds. Were analyzed for this yellow-fleshed peaches of two cultivars: cv. Granada and cv. Diamante, harvested at three ripening stages: green, ripe and overripe. To determine the maturity stages of fruits were evaluated color parameters of skin, firmness, titratable acidity, total acidity and soluble solids. For the functional properties, were assessed the levels of carotenoids, levels of phenolic compounds and antioxidant activity in edible part of fruit. The results showed that peaches harvested at early stages of maturity had higher values of firmness and the greatest amount of phenolics compounds. The fruits harvested more mature showed reduction in the firmness and lower nutritional characteristics.